"Where ignorance is bliss, 'tis folly to be wise": Indiscriminate male care in a neotropical spider. (20th November 2020) - Moura, Rafael Rios; Oliveira, Isabella Dias; Vasconcellos‐Neto, João; Gonzaga, Marcelo Oliveira
Abstract: Certainty of paternity is considered an important condition for the evolution and maintenance of extended male care. In some species, males may cannibalize unrelated offspring or abandon the progeny when the uncertainty of paternity is high, or when they take over nest sites or females from other males. However, male protection of offspring can also evolve in situations of uncertainty of paternity, especially when males cannot recognize offspring relatedness. In such cases, males may take care of all their mate's offspring, regardless of paternity. In Manogea porracea (Araneidae), the only known spider species where males care for offspring, males repel competitors by assuming and defending specific positions within a female's web, but females accept multiple partners during the reproductive season. Consequently, males may care for some offspring produced with the sperm of their mate's previous partners. If males cannot detect offspring relatedness, we expect that they will not cannibalize progeny and will actively protect all offspring against predation. The main goal of this study was to investigate whether the extended male care depends on offspring relatedness recognition. Therefore, we experimentally manipulated offspring relatedness and the presence of foster males and two egg predators usually found invading M. porracea webs. We also compared our results with data from an experiment performed by Moura, Vasconcellos‐Neto, & Gonzaga (2017) using the same laboratory procedures, but introducing egg sacs fathered exclusively by the males. Males did not cannibalize offspring and protected the progeny against predation regardless of offspring relatedness. In addition, all males moved the egg sacs to the center of the web, remaining close to the progeny. We conclude that M. porracea males protect all progeny present in their partner's web and increase offspring survivorship regardless of relatedness. We discuss the behavioral and evolutionary implications of our findings, and potential triggers of male care in M. porracea . Abstract : In some cases, paternal care can evolve under uncertainty of paternity, especially when males cannot recognize offspring relatedness. Evidence for parental recognition in spiders is mixed, and paternal care is rare. Manogea porracea (Araneidae) is the only spider species described to the date in which males exhibit exclusive paternal care. In this experimental study, foster males assumed a protective position, bellow the progeny. They defend unrelated offspring against two araneophagic spider species as effectively as the biological fathers, increasing offspring survival compared to treatments without parental protection. Thus, M. porracea males cannot discriminate offspring relatedness.